COVID-19, Stock Market Crisis and Investor Sentiment: French and USA Case - AHMED, Dalenda Ben; HENCHIRI, Jamel Eddine (Journal of Ecohumanism, 2025)
Purpose: This work is part of the behavioral literature, whose objective is to evaluate the capacity of investor sentiment to predict the Covid-19 crisis on the French and American stock markets. Design/methodology/approach: Our study is based on all companies listed in the CAC40 index for France and the Dow Jones index for the US during the first half of 2020, when the Covid19 pandemic started. The statistical methods "Time Series" model used to test our hypothesis on the contribution of investor sentiment, the interest rate and the inflation rate to development of stock market crises. Findings: The results show that the Covid-19 crisis is positively and significantly explained by investor sentiment. While,the interest rate and inflation negatively influence the probability of a stock market crisis. The results also show that the inclusion of psychological factors improves the explanatory power of our alert model and proves to be effective in predicting stock market crises. Originality: This work can be considered as the first one to evaluate the cointegration between the Covid-19 crisis and the investor’s sentiment.